Taking instructional coaching up a notch: the impact of BDI on vocabulary teaching and learning - Intriago-Palacios, Éder A. (Kansas State University, 2021)
This quantitative study was designed to examine Biography-Driven Instruction Coaching’s effect on increasing English vocabulary by third grade emergent bilinguals in Ecuador. The review of the literature on instructional coaching as a form of teacher professional development shows it has not been extensively researched; less so used in combination with the Biography-Driven Instruction method, as an EFL method with emergent bilinguals. One of the main purposes of this study was to accelerate language proficiency in emergent bilinguals by coaching EFL teachers by using Biography-Driven Instruction Method. This research and its experiment were meant to create a precedent study that would be followed by researchers and teaching professionals to examine, explore, and manage teacher professional development processes aimed at impacting student achievement. The research question and the hypotheses were examined through a quantitative research study, which followed a non-randomized control trial design. The study participants were on the one hand, EFL teachers form public schools located on the west coast of Ecuador, and their emergent bilinguals. Emergent bilinguals in experimental and control groups were assessed at two points to determine whether there was a difference in the gained scores on the posttest. Six lesson plans based on the principles of the Biography Driven Instruction method were designed and applied by EFL teachers in partnership with an instructional coach, to increase the level of performance measured by the Pre-A1 Starters. A control group was used to measure the effectiveness of the intervention. Vocabulary learning is an important part of learning to read and learning to communicate appropriately. Its teaching requires research-based and theory-driven strategies which the Biography-Driven Instruction method, is argued here, may help accelerate. Through quantitative data collection, organization and statistical analysis, it was discovered that there was no statistically significant effect of BDI coaching on the vocabulary scores obtained by the emergent bilinguals in the experimental group. The findings of this study, despite this unexpected result, might render an additional support to the theory of instructional coaching as an effective way of providing teacher professional development when used in combination with a method of instruction that attends to the biographies of the EFL teachers. Finally, this study raises awareness among EFL professional developers of the use of instructional coaching, in combination with tenets from the Biography Instruction Method, as more robust way of providing quality instruction. Both EFL teachers and the coach partner up towards a common goal: helping emergent bilinguals succeed. Through this study, teachers’ professional developers might continue their search of effective ways to aid EFL teachers in providing quality instruction. In turn, EFL teachers may see in the assistance from a coach and in the BDI method a new avenue for meeting their aspirations to produce higher student achievement. And emergent bilinguals from all primary school grades may find in this powerful coach-teacher combination a possible long-term solution to advancing their pluricultural and plurilingual competence.
Keywords: Instructional coaching; Biography driven instruction; Emergent bilinguals; EFL; Vocabulary